Peningkatan Etika Bertegur Sapa Anak Usia 5-6 Tahun Melalui Lagu “Budayakan 5S” - Nopiyanti, Heni; Jannah, Miftachul; Enjang, Enjang (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
These This study aims to improve the etiquette skills of greeting in children aged 5-6 years using the "Budayakan 5S" song media. This research uses a quasi-experimental design model. The research subjects were 36 students from group B1 and B2 of RA Baetul Ghofur. Data collection techniques used validated observation sheets. This study aims to determine the effect of learning using the "Budayakan 5S" song on improving etiquette skills in early childhood at RA Baetul Ghofur. The method used is an experiment with a pre-test and post-test design on the experimental class and control class. The research approach used is quantitative descriptive. The results of data analysis show a significant increase in the post-test scores of the experimental class compared to the control class. This proves that the use of the "Budayakan 5S" song as a learning medium is effective in improving etiquette skills in early childhood.